Informe del vivero de adaptacion centroamericano VIDAC 1987 - Orozco S., S.H.; Beebe, Stephen E.; Dessert, J.M. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
This nursery was organized in response to the need for improving adaptation and obtaining genetic information on the resistance or reaction to the different stress environments (biotic and abiotic) to which beans are subjected in production areas. Results are given for the best black- and red-seeded lines of the 1987 VIDAC, covering characteristics such as 100 seeds, days to flowering and physiological maturity, wt. of and response to diseases such as rust (Uromyces phaseoli), bacterioses (Xanthomonas phaseoli), BGMV, and web blight (Thanatephorus cucumeris). The yield potential and genetic adaptation of the best materials over different sites are also analyzed. Information on these national and regional trials should be collected in an efficient regional information and documentation center. (CIAT)